Methodology for assessing the spherical plain bearings durability - V. K. Harina; O. A. Ratenko; G. B. Vardanyan (Научный вестник МГТУ ГА, 2025)
The article presents an improved method for assessing the durability of spherical plain bearings, operating under the conditions of oscillatory motion, based on the processing of an array of experimental data obtained in laboratory conditions as well as during operation of the product. One of the options of mathematical modeling was applied, which uses regression methods to approximate the function of one variable. As an object of research, spherical plain bearings installed in aircraft (engine) control systems and operating in cyclic rocking motion are considered. Spherical bearings are plain bearings, and the amplitude of their rocking movements can vary over a wide range from ±20° to ±60°. The problems of calculating the service life of plain bearings are well studied and documented in the relevant standards GOST 1144-75 “Rolling bearings. Methods for calculating durability”, GOST 15084-78 “Plain bearings. Methods for calculating durability”. Spherical bearings are plain bearings, but at the same time, there are many technical applications in which bearings operate under conditions of oscillatory motion, for example, in flap drive units, in aircraft control systems, etc. Features of operating conditions determine the specific types of defects identified in experimental studies. It is shown that the known methods for calculating the durability of plain bearings do not allow obtaining acceptable practical results in assessing the service life of bearings operating in cyclic rocking motion.